PENGEMBANGAN MEDIA POP UP BOOK DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM DI KELAS III UPT SPF SDN BALANG BODDONG KOTA MAKASSAR - Mardani, Izmy Dewi; Pattaufi; Farida Febriati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning Natural Science in third-grade classes often encounters challenges due to the lack of engaging and easily understandable learning media. Many abstract concepts are difficult for students to comprehend through verbal explanations or textbook text, resulting in reduced learning motivation. This study aims to: (1) Identify the need for Pop-Up Books, (2) Design Pop-Up Books, (3) Evaluate the validity of the Pop-Up Books, and (4) Assess the practicality of the Pop-Up Books.The research follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and was conducted at UPT SPF SDN Balang Boddong with 29 students and one third-grade teacher as participants. Data were collected using questionnaires to identify students' and teachers' needs, content and material expert validation, media validation, small-group testing (beta 1), large-group testing (beta 2), and supporting documentation. The data were analyzed using qualitative descriptive and statistical descriptive methods. The results indicate that 90% of students found the Pop-Up Book highly needed, and 80% of teachers agreed it was necessary. Content and material expert validation scored 98% (highly valid), while media validation scored 86% (valid). Small-group testing achieved 85% (practical), and large-group testing reached 91% (highly practical). In conclusion, the Pop Up Book developed in this study is valid and practical for use in teaching Natural Science to third-grade elementary school students.